Chili Seed (Capsicum frutescens) Viability Using Radical Emergence with Correlation to Germination - Undang; Nurhosiah, F; Setyono; Yuliawati (Indonesian Journal of Applied Research (IJAR), 2026)
Chili peppers are a very popular horticultural commodity among Indonesians. The high demand for chili peppers in Indonesia has led to a continuous increase in chili production, making them a valuable commodity. This is due to their distinctive flavor and limited availability. This study aimed to determine the effect of genotype on root emergence time, which correlates with growth capacity and can be used to estimate seed quality. The experiment was designed using a completely randomized design. This study used 10 chili pepper genotypes with 3 replications, resulting in 30 experimental units. Each experimental unit consisted of 25 seeds, resulting in 750 observation units. The observed variables include seed testing in the laboratory: radicle emergence (RE), mean germination time (MGT), germination power (GP), maximum growth potential (MGP), sprout growth rate (SGR), growth speed (GS), uniformity of growth (UG), dry weight of normal sprouts (DWNS), vigor index (VI) and greenhouse testin: seed germination (SG). The results of the radicle emergence test had a very strong positive correlation with seed viability and seed vigor tests, namely GP (r = 0.809), RE (r = 0.895), and UG (r = 0.877). However, RE has a weak correlation with SG (r = 0.138) in the field. Chili seed testing using the radicle emergence test method is carried out by counting the number of radicles that emerge after 120 hours (5 days) of germination. This method is faster than the germination test, which takes 14 days.